2019
DOI: 10.1136/postgradmedj-2018-135995
|View full text |Cite
|
Sign up to set email alerts
|

Overutilisation of imaging studies for diagnosis of pulmonary embolism: are we following the guidelines?

Abstract: ObjectiveTo evaluate if imaging studies such as CT pulmonary angiography (CTPA) or ventilation–perfusion (V/Q) scan are ordered according to the current guidelines for the diagnosis of pulmonary embolism (PE).MethodsWe performed a retrospective observational cohort study in all adult patients who presented to the Sparrow Hospital Emergency Department from January 2014 to December 2016 and underwent CTPA or V/Q scan. We calculated the Wells’ score retrospectively, and d-dimer values were used to determine if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
3
20
1
Order By: Relevance
“…This study identifies an overutilization of CTPA examinations in Edmonton emergency departments, which is congruent with several other studies across the world [4,6,8,10,15,16], most recently shown in a large retrospective cohort out of Michigan in 2018 [17]. We found 26.7% of CTPA studies did not follow a CDM tool, despite evidence and guidelines recommending CDM tools over clinical gestalt [68].…”
Section: Discussionsupporting
confidence: 89%
“…This study identifies an overutilization of CTPA examinations in Edmonton emergency departments, which is congruent with several other studies across the world [4,6,8,10,15,16], most recently shown in a large retrospective cohort out of Michigan in 2018 [17]. We found 26.7% of CTPA studies did not follow a CDM tool, despite evidence and guidelines recommending CDM tools over clinical gestalt [68].…”
Section: Discussionsupporting
confidence: 89%
“…Our study shows that the detection of PE on CTPA in a tertiary care centre in the USA is 10.9% and not as low (<1%) as shown18 in a recent study from a similar tertiary care centre in the USA. The positivity in our study is similar to other previous studies which showed a yield ranging from 6% to 34%, with positivity of 10% or more generally considered acceptable in the USA 19–21.…”
Section: Discussioncontrasting
confidence: 53%
“…An Australasian multicenter trial22 and British Royal College of Radiologists23 have used a cut-off of CTPA positivity greater than 15.4% as a standard-of-care. Most of the studies with less than 10% yield are from the USA,24 with at least two studies showing positivity less than 2% 18 25. This is in contrast to European studies showing a yield well over 10% 26–28.…”
Section: Discussionmentioning
confidence: 93%
“…By continuously monitoring the on-call workload, radiology departments can implement workload-reducing strategies in a timely manner. Medical imaging overutilization is a well-known problem which may have contributed to the increasing on-call workload [18][19][20][21]. Radiologists and radiology departments can play an active role to decrease medical imaging overutilisation by providing education and feedback to referring physicians [22,23].…”
Section: Discussionmentioning
confidence: 99%